Anti-Listerial Activity Control of Postbiotic in Cow Milk Lump Cheese Processing - Laukova, Andrea; Burdova, Oľga; Korenekova, Beata (European Journal of Applied Sciences, 2023)
Nowadays, a new approach has been focused on the food safety maintenance using postbiotics (antimicrobial peptides-bacteriocins). This approach involves also use of postbiotics where bacteriocins are included. Here Enterocin A/P (isolated and studied at our laboratory) was applied in cow milk lump cheese inoculated with Listeria innocua LMG 13568. Enterocin A/P was found with reducing tendency against L. innocua LMG 13568 in cow milk lump cheese (differences 1.0 - 0.42 log cycle) using the standard microbial method. Direct anti-listerial activity of Enterocin A/P in cheese was not found. The acidity parameters (pH, ˚SH) were well balanced, not influenced (pH) and/or continually increased (˚SH) with Enterocin A/P treatment and LMG 13568 strain inoculation. Additional studies are requested; however, postbiotic-dipeptide Enterocin A/P showed beneficial antimicrobial potential tendency in cow milk lump cheese.